Daily Activity Patterns and Feeding Behavior of Captive Ring-Tailed Lemur Lemur catta (Primates: Lemuridae) at the Schmutzer Primate Center, Ragunan Zoo, Indonesia - Syafutra, Randi (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2025)
This study investigates the daily activity patterns and feeding behavior of captive ring-tailed lemurs Lemur catta housed at the Schmutzer Primate Center, Ragunan Zoo, Indonesia. Through systematic observation over two months, including Ad Libitum and Focal Animal Sampling methods, data were collected on three adult individuals (one female and two males). Results revealed a predominant time allocation to resting (72.6%), followed by grooming (9.81%), locomotion (8.20%), and feeding (8.15%). Feeding activity peaked in the morning and late afternoon, aligning with thermoregulatory behavior such as sunbathing. The lemurs displayed a preference for provisioned fruits and vegetables, with limited manipulation of food items, reflecting species-specific feeding traits. No occurrences of agonistic, sexual, or play behaviors were recorded during the observation period. These findings highlight the behavioral adaptations of L. catta in a semi-natural captive setting and provide essential insights for enhancing animal welfare, enrichment, and management practices in zoological institutions. Keywords: daily activity pattern, feeding behavior, Lemur catta, ring-tailed lemur, Schmutzer Primate.